Aktuelle Aspekte zur Ototoxizität: lokale ototoxische Wirkungen, Diagnostik, Prävention und Therapie = Current aspects of ototoxicity - Walther, Leif Erik; Hülse, Roland; Lauer, Katrin; Schell, Angela (HNO, 2015)
The otorhinolaryngologist is often involved in an interdisciplinary approach to diagnose ototoxic side effects. Under certain conditions, chemical agents—particularly drugs—can have ototoxic effects. This is not only true for systemic administration, but also for local application (e.g., transdermal and transtympanal). Identifying and avoiding ototoxicity is still a challenge in clinical practice. The audiological monitoring of patients receiving potentially cochleotoxic drugs is now standardized. For diagnosis of suspected vestibulotoxic effects, the video head impulse test and vestibular evoked myogenic potentials seem to be suitable procedures for objective assessment. The early detection of such ototoxic effects has important implications for the prevention of hearing and balance disorders. Recent studies show that intratympanic delivery of medications might play an important role in the limitation of ototoxically induced hearing loss. In peripheral vestibulopathies with episodic vertigo, which strongly affect quality of life, ototoxic effects can be used for therapeutic purposes.